Economic evaluation of chronic lymphocytic leukemia from a hospital management perspective. (1st November 2016) - Kron, Florian; Kutsch, Nadine; Kostenko, Anna; Dohle, Ines; Glossmann, Jan‐Peter; Müller, Dirk; Heimann, Sebastian M.; Bahlo, Jasmin; von Bergwelt‐Baildon, Michael; Eichhorst, Barbara; Wolf, Jürgen; Hallek, Michael; et al.
Abstract: Objectives: Treatment of chronic lymphocytic leukemia (CLL) is currently undergoing dramatic changes. We analyzed economic risks in hospitalized patients with CLL from a management perspective. Methods: One hundred and twelve patients with CLL hospitalized in 2013 and 2014 at the University Hospital of Cologne were analyzed. To assess profit margins (PMs) per case, diagnosis‐related group (DRG) reimbursement data were merged with an internal cost accounting scheme depending on age, prognostic factors, and DRG key performance indicators. Results: In 112 patients, 284 cases coded by 19 different DRG with strongly fluctuating cost revenue ratios were found with an overall negative PM of €137 147. The DRG R61H was identified as the one most commonly coded (174 cases, 61.3%) with a deficit per case of €814. Subanalysis demonstrated that the payments were not cost covering due to excessive length of stay and staff costs. Significant differences in PM per case concerning age, length of stay and number of operation and procedure key (OPS) codes ( P < 0.05) were found. Conclusion: In our research‐driven tertiary care hospital, inpatient treatment of patients with CLL is not cost covering. This analysis demonstrates the need for novel care/reimbursement structures in CLL. From a hospital management perspective, cost revenue controlling is crucial to avoid major economic risks.